Polyvinyl chloride (PVC) derived microporous carbons prepared via hydrothermal dechlorination and potassium hydroxide activation for efficient CO2 capture. (July 2023) - Yang, Fangming; Liu, Xin; Li, Mengbin; Uguna, Clement; Wang, Wenlong; Sun, Chenggong
Abstract: Hydrothermal dechlorination has been widely studied for recycling end-of-life polyvinyl chloride while the impact of embedded metal additives, a major component of many waste PVC products, has rarely been reported. In this study, hydrothermal treatment of used polyvinyl chloride pipe was carried out at a temperature range between 220 and 280 °C to understand the role of metal additives in the dechlorination process. The potential application of chlorine-free hydrochar as the precursor to prepare CO2 sorbents via chemical activation was also evaluated. The results demonstrated that the well-distributed calcium carbonate in the polyvinyl chloride matrix, acting as an in-situ neutralization agent, could accelerate the dechlorination of PVC, over 98.4% of chlorine was removed at 260 °C or higher. Using the hydrochar prepared at 260 °C as a single precursor, a series of activated carbons were successfully prepared via a facile chemical activation process. Those hydrochar-derived carbons have a microporous dominant structure with high surface area and total pore volume reaching up to 1927 m 2 g −1 and 0.85 cm 3 g −1, which showed great potential as CO2 sorbents. Tested at 25 °C, the microporous carbons exhibited both remarkable CO2 adsorption capacities of 1.60 mmol g −1 and 4.05 mmol g −1 at 100 kPa and high CO2 /N2 selectivity of 42 at 15 kPa CO2 . Advanced characterization demonstrated that the excellent CO2 adsorption performance originated from a unique combination of ultra-microporosity and surface chemistry. This work provides an effective and sustainable strategy to recycle hard-to-handle chlorinated plastic waste and reduce carbon emissions. Graphical abstract: Image 1 Highlights: Hydrothermal treatment of PVC containing additives (20 wt%) was carried out. The in-situ CaCO3 could accelerate the dechlorination of PVC under mild conditions. Microporous carbons were successfully prepared by using PVC derived hydrochar. HPVC carbons exhibit superior CO2 uptake and CO2 /N2 selectivity at 25 °C.